2018
DOI: 10.1111/jir.12532
|View full text |Cite
|
Sign up to set email alerts
|

Access to assistive technology for people with intellectual disabilities: a systematic review to identify barriers and facilitators

Abstract: Background The World Health Organisation has launched a programme to promote Global Cooperation on Assistive Technology. Its aim is to increase access to high-quality affordable assistive products (AP) for everybody in need. People with intellectual disabilities (ID) are a specific group that could benefit from AP, but use less AP compared to their non-intellectual disabled peers. Method A systematic literature search was carried out to identify barriers and potential facilitators for access to AP for people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 43 publications
(87 reference statements)
1
67
0
7
Order By: Relevance
“…Public funding was found to be segmented; different types of impairment may have different funding systems to acquire AP with funding dependant on both the number of people and the annual budget of the public funding authority within an area. Funding is known to be one of the main barriers to AP access for people with ID [22]. Fundamentally, the segmented and disjointed aspect of public funding found in this study is a key issue for policy makers who aspire to adhere to implementing the UNCRPD equally in all areas of their country.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Public funding was found to be segmented; different types of impairment may have different funding systems to acquire AP with funding dependant on both the number of people and the annual budget of the public funding authority within an area. Funding is known to be one of the main barriers to AP access for people with ID [22]. Fundamentally, the segmented and disjointed aspect of public funding found in this study is a key issue for policy makers who aspire to adhere to implementing the UNCRPD equally in all areas of their country.…”
Section: Discussionmentioning
confidence: 81%
“…The International Classification of Functioning, Disability and Health (ICF) addresses barriers as factors in a person's environment which limit functioning and create disability, while facilitators are factors that improve functioning and reduce disability [21]. A recent systematic review by Boot et al identified the currently available scientific evidence on barriers and facilitators for people with ID to access AP [22]. The three main barriers found in literature were related to AP costs, lack of awareness about AP, and inadequate assessments for people with ID.…”
Section: Introductionmentioning
confidence: 99%
“…The barriers to technology use among people with disability have been well-documented across a range of populations. In a recent systematic review [8] of assistive technology use by people with intellectual disability, 22 studies collectively identified 77 barriers and 56 facilitators. The most frequent barriers were associated with lack of funding and cost, lack of awareness about technology and inadequate assessment of need.…”
Section: The Technology Challenge In Rehabilitationmentioning
confidence: 99%
“…Esses dispositivos podem ser planejados ou adaptados para ajudar pessoas deficientes intelectuais na comunicação diária, na independência, no aprendizado e nas atividades sociais como os jogos, por exemplo. [1,3,12,13,20] O objetivo da Tecnologia Assistivas, quando aplicado na área da educação, é uma estratégia para o aluno realizar o que precisa. Valoriza o seu jeito de fazer e criar novas alternativas para comunicação, mobilidade, interação social, resolução de problemas e brincadeiras.…”
Section: Introductionunclassified
“…Com isso, tem-se dado uma maior atenção ao potencial que a tecnologia assistiva tem em propiciar independência e autonomia para deficientes intelectuais, por meio de jogos educacionais. [1,3,12,13,20] Nesse contexto, os jogos educacionais digitais são considerados como ferramenta de apoio ao aprendizado de Pessoas com Necessidades Educativas Especiais (PNEE).…”
Section: Introductionunclassified